2016
DOI: 10.1016/j.physbeh.2015.11.019
|View full text |Cite
|
Sign up to set email alerts
|

No effects of ingesting or rinsing sucrose on depleted self-control performance

Abstract: 15Self-control tasks appear to deplete a limited resource resulting in reduced subsequent self-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 49 publications
(6 reference statements)
0
10
0
Order By: Relevance
“…This fall in plasma glucose could reflect a more efficient transfer of glucose to the brain which in turn results in increased provision centrally (62) . One should be cautious when making assumptions about peripheral blood glucose levels and their putative effects on the brain, as other studies have failed to demonstrate such findings (73,74) . Nevertheless, the evidence suggests that cognitively demanding tasks and in particular those relying on executive functions are sensitive to changes in glucose availability (70,75) .…”
Section: Acute Administration Of a Glucose Load: Prototypical Experimmentioning
confidence: 99%
“…This fall in plasma glucose could reflect a more efficient transfer of glucose to the brain which in turn results in increased provision centrally (62) . One should be cautious when making assumptions about peripheral blood glucose levels and their putative effects on the brain, as other studies have failed to demonstrate such findings (73,74) . Nevertheless, the evidence suggests that cognitively demanding tasks and in particular those relying on executive functions are sensitive to changes in glucose availability (70,75) .…”
Section: Acute Administration Of a Glucose Load: Prototypical Experimmentioning
confidence: 99%
“…Furthermore, it is possible that self-control depletion is not determined by inadequate brain glucose supply during exertion of self-control, and numerous theories have risen to explain the depletion effect sans brain glucose depletion (e.g., Inzlicht and Schmeichel, 2012 ; Kurzban et al, 2013 ; Ampel et al, 2016 ). Research has suggested that participants who gargle with glucose, but do not consume it exhibit attenuation of the depletion effect (e.g., Sanders et al, 2012 ; Carter and McCullough, 2013 ; Hagger and Chatzisarantis, 2013 ; but see Lange and Eggert, 2014 ; Boyle et al, 2016 ), and new meta-analyses go so far as to provide evidence that glucose administration does not actually ameliorate the depletion effect at all ( Dang, 2016 ). These findings do not factor into our paper, as our objective is entirely concerned with addressing the inaccuracies that have occurred in the process of criticizing the biological plausibility of the glucose model of self-control depletion.…”
mentioning
confidence: 99%
“…36 For example, in alcohol research, studies have shown that participants who receive a placebo drink may improve behavior in social situations and performance because they try to compensate for expected cognitive impairment and they reinforce their attention to situational cues(Testa et al 2006). Molden et al (2012),Sanders et al (2012),Boyle et al (2016) andDang (2016) have shown a variety of placebo effects in the domain of self-control and resource consumption.37 So the maximum they can borrow is €1000/1.15 €870.…”
mentioning
confidence: 99%